Sosialisasi Kandungan QS. Al-Hujurât Ayat 12 dalam Tafsir As-Sa'diy Di Desa Pekan Sawah Kecamatan Sei Bingai Kabupaten Langkat - Syahrul Holid; Juliani Juliani; Yandi Irawan (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
This community service is to increase awareness of the importance of practicing the values ​​contained in the Qur'an and as-Sunnah, including the Socialization of the Content of QS. Al-Hujurât Verse 12 in Tafsir As-Sa'diy. The choice of this verse is motivated by the phenomenon that most people fall into actions that should be shunned when interacting with society, such as prejudice (sû'uzhan), finding fault with others (tajassus), and no less important is backbiting (ghîbah) between one another. other. The methods used in this community service activity are survey methods, scientific seminars, discussions and questions and answers. The results of this community service showed that almost all participants who attended had understood well the contents of the QS. Al-Hujurât in the interpretation of As-Sa'diy. This can be seen from the enthusiasm of all seminar participants during the activity. Awareness about the importance of protecting the rights of fellow Muslims and staying away from actions that are prohibited by Allah SWT, such as the prohibition of sû'uzhan, tajassus, and backbiting is the main message contained in QS. Al-Hujurât verse 12 as explained by Syaîkh Abdurrahmân ibn Nasir As-Sa'diy in his commentary. In the end, a good understanding of this verse needs to be internalized in a real and consistent way in everyday life because charity is the fruit of knowledge itself